Femtosecond laser induced robust Ti foam based evaporator for efficient solar desalination. Issue 14 (19th March 2019) - Yin, Kai; Yang, Shuai; Wu, Junrui; Li, Yejun; Chu, Dongkai; He, Jun; Duan, Ji-An
Abstract : We report a simple, efficient method to prepare a Ti foam-based evaporator for efficient solar evaporation and desalination. Abstract : Solar desalination is a sustainable, low-cost and eco-friendly method for water purification. Current methods for solar evaporation desalination suffer from relatively low efficiencies, complex preparations, high cost, and instability. Here, for the first time, we propose a femtosecond laser structured Ti foam for use in a rapid steam escaping evaporator for solar steam generation. The assembled device has a high water evaporation rate of ∼1.79 kg m −2 h −1 and a solar steam efficiency of ∼90% under one sun irradiation. The device is constructed from a treated Ti foam, insulation cotton and polyurethane sponge. The treated Ti foam possesses efficient broadband solar absorption (>97%), Janus characteristics (superhydrophilicity/hydrophobicity) for pumping water on the vapor surface, and superaerophobicity for rapid vapor release, all of which facilitate confined water evaporation. The underlying insulation cotton alleviates thermal dissipation. The pre-wetted polyurethane sponge supplies water to the Ti foam, thus avoiding direct contact between the treated foam and bulk water. Promisingly, a home-made system was built to verify the feasibility of generating purified water. The femtosecond direct writing technology provides a rapid approach for efficient desalination using natural sunlight.